ANALISIS PERDAGANGAN INTERNASIONAL STUDI KASUS PERKEMBANGAN EKSPOR KOMODITAS LEMAK DAN MINYAK HEWANI ATAU NABATI (KODE HS 1518) PROVINSI SULAWESI BARAT - Riady Ibnu Khaldun (Jurnal Bina Bangsa Ekonomika, 2024)
Trade can be interpreted as a form of interaction carried out by certain actors to fulfill their needs. Often, in the international scope, the parties interacting within it are more easily categorized between one country and another, but more specifically, they are business actors in each country. Likewise, Indonesia can be said to have carried out a lot of international interaction or trade with other countries, both bilaterally and multilaterally. If studied more deeply, it can be understood that there are various types of commodities traded, including each region that contributes to it. One of them is that West Sulawesi Province also has superior products that are traded internationally or globally, not only in imports, but also in the form of exports. Available data shows that West Sulawesi Province has superior commodities but in non-oil and gas form, namely Animal or Vegetable Fats and Oils (HS Code 1518). In recent years, it has been shown that this commodity has an important role in supporting the increase in the export value of West Sulawesi Province, namely 430 million US$ in 2018, 459.2 million US$ in 2019, 503 million US$ in 2020, and 647 million US$ $ in 2021 where 91.65% of the province's export commodities are animal or vegetable fats and oils. The West Sulawesi government can provide support through policies, infrastructure development and export promotion to encourage increased exports of these commodities